Organisational efficacy and the role of management control system in construction industry / Nur Arfah Mustapha and Roshidi Hassan. - Mustapha, Nur Arfah; Hassan, Roshidi (Universiti Teknologi MARA Selangor, 2017)
Management control system is putatively vital for management to resemble organisational performance.The objective of the study is to understand the role of management control system in organizational efficacy. Management control system has obtained growing attention within both academia and industry as part of OE. As works of literature grow, finding new directions by critically evaluating the research and identifying future trends has become central in advancing knowledge for the field. This paper will review some of the work done in this area of study. Applying management control system as a theoretical lens, we develop a research plan from current OE and management control system literature by offering propositions for future research where management control system may permeate contemporary OE topics. In doing so, we provide an initial foundation for organisational efficacy scholars to both incorporate the role of management control system effects into research and launch new research stream.